Research progress of health action process approach model in nursing interventions for patients with type 2 diabetes mellitus (健康行动过程取向理论模型在2型糖尿病护理中应用的研究进展) - ZHANG Jiahui (张家慧); WANG Yan (王艳) (中西医结合护理)
Diabetes mellitus is one of the most prevalent diseases affecting the endocrine system, associated to high morbidity, disability, and mortality rate. Active lifestyle interventions are potentially effective to improve the prognosis of patients with diabetes mellitus. The health action process approach model (HAPA) is a social-cognitive model specifying motivational and volitional determinants of health behavior, and the process of HAPA consists of a motivation, volition and action phase. The HAPA model can be used in the behavior prediction and explanation, scale development, path analysis and intervention studies for patients with type 2 diabetes mellitus. According to the prediction, explanation and analysis of patients’ behavior, a nursing and health education plan based on the HAPA model is recommended for diabetes care in clinical practice and research. (糖尿病是一种常见的内分泌系统疾病, 具有高发病率、致残率和死亡率。积极的生活方式干预对糖尿病患者的发展及预后有促进作用。健康行动过程取向理论模型(HAPA)是一种较新的社会认知理论, 分动机阶段、意向阶段和行动阶段。该理论可用于2型糖尿病(T2DM)相关行为的预测、解释、量表的编制、路径分析及干预研究。运用HAPA模型预测、解释、分析糖尿病患者的行为, 构建基于HAPA模型的护理干预方案及健康教育方案, 能够为糖尿病患者的护理提供参考依据。)